Análise econômica da produção industrial de frangos de corte: estudo sob a ótica do produtor integrado - Edgard Onoda Luiz Caldas (2014)
The aim of this study was analyze the economic situation of integrated broiler producers and compare economics and performance indicators obtained in two technological options of sheds acclimatization. Data about performance indicators, costs and revenues were collected every production cycle, during 18 months in eight properties located in Prados - MG and Pratania - SP. In the case study I the economic evaluations were conducted on eight properties based on the average of seven production cycles for each, resulting in 56 production cycles. In the case study II data from 42 cycles obtained on six properties located in Prados MG were used, half of them with negative pressure sheds and the other ones with positive pressure acclimatization. Comparisons between technologies were made from the average from 21 cycles for each acclimatization technology. In case study I was found that economic success in poultry production depends on optimizing use of inputs, fixed assets and services, without disregarding technical concepts that may affect the performance of the birds. In case study II was found that controlled negative pressure systems are better economic alternatives for the rearing of broilers in comparison with positive pressure. The highest yield obtained per square meter in negative pressure sheds was directly related with the dilution of fixed and variable costs. Moreover, the average revenue obtained in this system was greater than that observed for positive pressure because of performance indicators presented by the birds. The market trend observed for poultry production was the expansion of activity with greater propensity to invest in negative pressure sheds, but the integration model does not enable the inclusion of small producers in the activity due to the high investments required for implementation of production systems. In both case studies there was a strong dependence of the activity by the proceeds on the sale of poultry litter, without which the activity becomes a worse economical alternative than the investment in fixed income funds. Thus, it was found that the production of broilers in the integration system is economically sustainable and does not compromise the poultry production supply chain. However, the maintenance of rural producers in the activity depends on high production efficiency, the rational and balanced use of production factors, advanced acclimatization technologies and secondary income of production process.